Effects of a mock-up force plate on riding technique and perception - a prerequisite for comprehensive biomechanical analyses in mogul skiing - Kurpiers, N.; Kersting, U. G.; McAlpine, P. R. (Science and Skiing IV, 2009)
INTRODUCTION: The assessment of biomechanical Parameters in freestyle skiing is of major importance as remarkable changes in equipment design and movement patterns (technique) have occurred in the past decade. Measurement Systems need to be designed to fulfill the requirements of reliable on-snow data collection[1]. Such advanced technologies have great potential but may be compromised by affecting riding style and skier perception by adding mass or changing the geometry of the ski-boot interface. The purpose of this study was to examine the effects of using a force measurement device on riding technique in mogul skiing. A simulated version of the device was positioned between ski boot and binding. The current study was designed as a prerequisite for further comprehensive biomechanical research in snow sports.